2015
DOI: 10.1108/mrr-06-2014-0139
|View full text |Cite
|
Sign up to set email alerts
|

Predicting determinants of Internet banking adoption

Abstract: Purpose – The purpose of this paper is to explore the main determinants of Internet banking users on the basis of literature of technology acceptance model (TAM). Understanding and predicting main determinants of Internet banking is an important issue for banking industry and users. Design/methodology/approach – Service quality and trust were incorporated in the TAM together with demographic variables. The data were collected using Googl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(17 citation statements)
references
References 48 publications
1
16
0
Order By: Relevance
“…Our findings demonstrated minimal or no differences between train and test errors (see Table 16), confirming a non-overfitting and non-underfitting model [108]. The neural network's efficiency and prediction accuracy is measured by the root mean square error (RMSE) PLOS ONE [114]. The findings (see Table 16) confirmed that the values of RMSE with minimal training and testing errors (see Table 16), indicating an optimal fit DNN model.…”
Section: Plos Onesupporting
confidence: 65%
“…Our findings demonstrated minimal or no differences between train and test errors (see Table 16), confirming a non-overfitting and non-underfitting model [108]. The neural network's efficiency and prediction accuracy is measured by the root mean square error (RMSE) PLOS ONE [114]. The findings (see Table 16) confirmed that the values of RMSE with minimal training and testing errors (see Table 16), indicating an optimal fit DNN model.…”
Section: Plos Onesupporting
confidence: 65%
“…Over the past few years the growth of information and communication technology in the global banking industry is accelerating (Sharma et al, 2017). The banking industry implements technology to achieve competitive advantage through a larger customer base and personalized banking services for reduced operational costs (Sharma, Govindaluri, & Al Balushi, 2015;Laukkanen, 2016). Consistent with resources-based theory, the company's resources can be a key driver in the performance and competitiveness of enterprises (Riahi- Belkaoui, 2003).…”
Section: Hypotheses Developmentmentioning
confidence: 99%
“…Bandura (1982) suggested the concept of self-efficacy as “the degree of power of an individual's trust in one's own ability to ask for completion.” Computer self-efficacy measures the trust level an individual has regarding the use of computer-based technologies to perform the required tasks (Bao et al , 2013). Computer self-efficacy is considered a major factor affecting consumers' choice to implement computer-related technologies (Sharma et al , 2015). In the cloud computing field, Yang and Lin (2015) noted that computer self-efficacy impacts consumers' expectations on the implementation and ongoing utilization of cloud storage resources in the future.…”
Section: Proposed Model and Hypothesesmentioning
confidence: 99%